2018
DOI: 10.1089/mdr.2017.0212
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of Daptomycin-Nonsusceptible Methicillin-ResistantStaphylococcus aureusClinical Isolates Among Daptomycin-Naive Patients in Korea

Abstract: This study was conducted to assess emergence of daptomycin-nonsusceptible (DAP-NS) phenotype in DAP-naive patients with invasive Staphylococcus aureus (ISA) infections in Korea. A total of 208 S. aureus clinical isolates were selected from a previous prospective study on ISA infections and evaluated for DAP-NS. Although DAP has never been introduced in Korea, five DAP-NS S. aureus strains (2.4%) were identified among 208 S. aureus strains collected from ISA infections. The DAP-NS phenotype was observed only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Previous studies have demonstrated that SNPs within specific domains of MprF are often associated with increased synthesis or translocation of positively charged L-PG, and thus contributes to HD-CAP resistance via charge repulsion mechanisms [ 32 , 34 , 35 , 38 ]. The two mprF SNPs (I375M and I461T) identified in the ST72 CA-/LA-MRSA strains in this study were reported in a previous publication in a daptomycin-nonsusceptible (DAP-NS) ST72 MRSA strain that displayed an enhanced surface positive charge versus DAP-susceptible MRSA strains [ 39 ]. However, in a recent publication [ 10 ], the 18 ST72 MRSA-IV strains with the I375M and I461T mutations were shown to have reduced levels of surface positive charge compared to those of the ST5 HA-MRSA strains.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Previous studies have demonstrated that SNPs within specific domains of MprF are often associated with increased synthesis or translocation of positively charged L-PG, and thus contributes to HD-CAP resistance via charge repulsion mechanisms [ 32 , 34 , 35 , 38 ]. The two mprF SNPs (I375M and I461T) identified in the ST72 CA-/LA-MRSA strains in this study were reported in a previous publication in a daptomycin-nonsusceptible (DAP-NS) ST72 MRSA strain that displayed an enhanced surface positive charge versus DAP-susceptible MRSA strains [ 39 ]. However, in a recent publication [ 10 ], the 18 ST72 MRSA-IV strains with the I375M and I461T mutations were shown to have reduced levels of surface positive charge compared to those of the ST5 HA-MRSA strains.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, to determine whether the I375M and I461T mutations in the mprF ORF are directly linked to the enhanced surface positive charge, and thus the HD-CAP resistance phenotype of ST5 HA-MRSA strains, the Newman ∆ mprF strains expressing the mprF genes from ST72 MRSA ( mprF I375M+I461T) or ST5 MRSA ( mprF ) strains were subjected to cytochrome c binding assays. As presented in Figure 1 , complementation of the Newman ∆ mprF strain with mprF I375M+I461T did not result in an enhanced surface positive charge versus the Newman ∆ mprF strain expressing a nonmutated form of mprF , suggesting that the two SNPs (I375M and I461T) are likely not involved in the previously observed increase in the surface positive charge of the ST5 HA-MRSA II strains [ 10 , 39 ]. Bayer et al also reported frequent SNPs within mprF ORFs among clinical DAP-NS MRSA strains, but only a limited number of SNPs within the hot spot loci of mprF were shown to be linked to the gain-of-function phenotype that resulted in enhanced surface positive charge [ 40 ].…”
Section: Discussionmentioning
confidence: 85%
“…Mutated genes and/or mutated gene patterns associated with isolates with the highest level of vancomycin resistance were not appreciably different than those found in isolates with a lower resistance, likely indicating that individual mutations played a large role in the resistance achieved versus genes overall. The cross-resistance of vancomycin and daptomycin in VISA strains has been well-studied (Cui et al, 2006;Nam et al, 2018). NRS70 and NRS384 endpoint strains were thus tested for development of daptomycin resistance by Etest.…”
Section: Resistance Phenotypes Of Evolved Visa Strainsmentioning
confidence: 99%
“…A total of 45 MRSA isolates derived from humans (n = 19), pigs (n = 14), and chickens (n = 12) were used in this study ( Table 1 ). All human and pig isolates were selected from previous studies [ 11 , 22 , 23 ]: eight isolates of ST5 HA-MRSA-II, eleven isolates of ST72 CA-MRSA-IV, eight isolates of ST398 LA-MRSA-V, and six isolates of ST541 LA-MRSA-V. As shown in Table 1 , MLST analyses revealed that 12 chicken-associated MRSA isolates were ST692 LA-MRSA-V and six ST188 LA-MRSA-IV. Except for eight ST5 HA-MRSA-II isolates, which belonged to agr type II, all other 37 MRSA isolates were agr type I.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 45 MRSA isolates of human and animal origin were used in this investigation ( Table 1 ). All human isolates were selected from two previous studies from our laboratory: eight ST5 HA-MRSA and eleven ST72 CA-MRSA isolates [ 22 , 23 ]. Nine ST398 LA-MRSA and six ST541 LA-MRSA isolates were selected from a previous investigation of LA-MRSA in healthy pigs [ 11 ].…”
Section: Methodsmentioning
confidence: 99%